COMMUNITY EMPOWERMENT AND DEVELOPMENT IN THE FIELD OF WOVEN BAMBOO CRAFTS THROUGH AN INTEGRATED MANAGEMENT SYSTEM - Anita Maleo,; Indriyani Abdul,; Abdul Rahmat,; Ummyssalam ATAD Duludu,; Pravin R. Choube, (International Journal of Innovations in Engineering Research and Technology, 2023)
The economic condition of the community which tends to be stagnant has resulted in Lembah Hijau Village having to be able to look for other opportunities to support an increase in the economic level of the community. Of the various livelihoods that exist in Lembah Hijau, woven craftsmen have considerable potential to help fulfill their daily needs. However, it is very unfortunate that the production process to the distribution of woven bamboo products is still very traditional and the producers face various obstacles. This study aims to describe how woven becomes a source of economic potential in improving people's lives. The method used is the method of analyzing local potentials and problems. The results of this study indicate that the woven bamboo industry has great potential if the local government and non-governmental organizations participate in empowerment training programs. more innovative and diverse so that their potential can develop from time to time.